Sections in Eugenia (Myrteae, Myrtaceae): nomenclatural notes and a key - Mazine, Fiorella F.; Bünger, Mariana Oliveira; de Faria, Jair Eustáquio Quintino; Lucas, Eve; Souza, Vinicius Castro (Phytotaxa, 2016)
Eugenia currently comprises c. 1050 species and is the largest angiosperm genus in Brazil. Recent morphological and taxonomic revision of Eugenia s.l. in light of current phylogenetic knowledge necessitates a new infra-generic classification. This study, based on available systematic data, circumscribes Eugenia in its current sense and provides detailed descriptions and illustration of the resulting nine infra-generic sections: Eugenia sects. Eugenia, Calycorectes, Hexachlamys, Phyllocalyx, Pilothecium, Pseudeugenia, Racemosae, Speciosae and the largest, Umbellatae that contains two thirds of the species in the genus. Relationships between Eugenia and Old World genera currently accepted as synonyms of Eugenia (Jossinia, Monimiastrum, Myrtopsis and Chloromyrtus) are also discussed. The paper presents a wide range of changes at the sectional level resulting in five new sectional synonyms, two new combinations, a lectotypification and one name of new status. An identification key to the sections is provided.